Consumer perceptions after long‐term use of alternative irrigation water: A field experiment in Israel. Issue 2 (17th March 2021) - Ellis, Sean F.; Kecinski, Maik; Messer, Kent D.; Lipchin, Clive
Abstract: This study provides the first revealed preference estimates of Israelis' willingness to pay for produce irrigated with alternative water. Results show that Israelis prefer produce irrigated with conventional water over any type of alternative water and that their preferences for alternative water varies by type. These results indicate that there may be long‐run limits to how high consumer demand for alternative water can rise. Policymakers should be cognizant of these findings and gradually expose the public to the unavoidable future of widespread alternative water use. Increased public awareness of water scarcity and alternative water technology will encourage adoption when it is possible and necessary.